2020
DOI: 10.3390/cells9102188
|View full text |Cite
|
Sign up to set email alerts
|

When the Search for Stemness Genes Meets the Skin Substitute Bioengineering Field: KLF4 Transcription Factor under the Light

Abstract: The transcription factor “Kruppel-like factor 4” (KLF4) is a central player in the field of pluripotent stem cell biology. In particular, it was put under the spotlight as one of the four factors of the cocktail originally described for reprogramming into induced pluripotent stem cells (iPSCs). In contrast, its possible functions in native tissue stem cells remain largely unexplored. We recently published that KLF4 is a regulator of “stemness” in human keratinocytes. We show that reducing the level of expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…As miRNA can regulate the protein transcription, we analyzed whether miRNA transferred within EVs can modulate the synthesis of its targets in normal keratinocytes. Indeed, the treatment of the Het1-A keratinocytes with "acidic" EVs significantly increased the expression of the miR-7 target-Krüppel-like factor 4 (KLF4)-regulating TGF-β and the WNT-signaling and differentiation in keratinocytes [58], both on the gene and protein levels (Figures 1b, S8 and S9c).…”
Section: Genementioning
confidence: 98%
See 1 more Smart Citation
“…As miRNA can regulate the protein transcription, we analyzed whether miRNA transferred within EVs can modulate the synthesis of its targets in normal keratinocytes. Indeed, the treatment of the Het1-A keratinocytes with "acidic" EVs significantly increased the expression of the miR-7 target-Krüppel-like factor 4 (KLF4)-regulating TGF-β and the WNT-signaling and differentiation in keratinocytes [58], both on the gene and protein levels (Figures 1b, S8 and S9c).…”
Section: Genementioning
confidence: 98%
“…Notably, the KLF-4 upregulation (Figure 1b) is in line with our observation of induction of the stem-like properties in the keratinocytes by "acidic" EVs. Despite the participation of KLF4 in the differentiation of the keratinocyte [58], it can also upregulate the transcription of many genes, indispensable for EMT and cell growth, so it also serves as an oncogene in many cancers [62,63]. Bio-plex analysis revealed that both types of EVs increased the phosphorylation of EGFR, mTOR, and ERK1/2 in the keratinocytes (Figure 5a,d,e).…”
Section: Metastatic Melanoma Evs Activate Intracellular Signaling Pat...mentioning
confidence: 99%